Impact of Fabrication Processes of Small-Molecule-Doped Polymer Thin-Films on Room-Temperature Phosphorescence - Thomas, Heidi; Haase, Katherina; Achenbach, Tim; Bärschneider, Toni; Kirch, Anton; Talnack, Felix; Mannsfeld, Stefan C. B.; Reineke, Sebastian (Frontiers in Physics, 2022)
The development of organic materials displaying room-temperature phosphorescence is a research field with growing interest over the last years. Here, the emitter molecule design is in the majority of research efforts in the focus of realizing an increase of phosphorescence lifetimes of host:emitter systems. Rarely, the overall thin-film system is optimized with respect to maximum triplet-state luminescence. Herein, the investigation of thin films consisting of N,N′-di(1-naphthyl)-N,N′-diphenyl-(1,1′-biphenyl)-4,4′-diamine (NPB) embedded in different polymer matrices is reported. Phosphorescence parameters such as phosphorescence lifetime, photoluminescence quantum yield and phosphorescence-to-luminescence ratio are determined and the importance of the film fabrication process is shown.